Influence of electron‑beam surfacing modes on thickness and uniformity of single‑layer coating when restoring parts made of titanium alloys - A. I. Pobol; V. G. Zaleski (Литьë и металлургия)
The influence of the beam current, the distance between the beads of the clad material and the wire feeding intensity during electron‑beam (EB) surfacing of titanium alloy VT9 on the thickness and uniformity of the resulting restoring coating was investigated. As the beam current strength increases, the width of the deposited layer increases and the height decreases. The optimal distance between the beads should be considered an offset that does not exceed the width of the bead. It is possible to control the height of the deposited layer in a wide range by precise dosing of the wire feed intensity. The uniformity of surfacing is ensured by a balanced energy impact. Chemical composition of the clad layer meets the requirements of normative documents on the content of impurity gases for products from medical materials, obtained by additive technologies. The results of the study are used in the restoration of the surface of the landing gear element of aviation equipment.